Natural fibres as reinforcement strategy on cork-polymer composites - Fernandes, E. M. (2013)
Cork powder, the most important sub-product of cork processing, combined with thermoplastic matrixes like, high density polyethylene (HDPE), offer a new class of cork-polymer composite (CPC) materials with high added-value. Therefore, reinforcing strategies must be considered to increase the mechanical performance, especially when high content of cork powder is added to the formulation. Coconut fibres have several advantages, such as, low density, renewable source, low cost and biodegradability. The use of these fibres on the reinforcement of CPC materials will not only contribute to improve the mechanical performance but also for increasing the amount of natural component present on the final composition. The main goal of this work was to prepare HDPE/cork (50-50 wt.%) composites reinforced with discontinuous coconut fibres (5 and 10 wt.%) with and without the addition of coupling agent (2 wt.%) by extrusion. The developed reinforced cork based composites were characterized regarding its morphology and mechanical performance. Optical micrographs have shown a homogeneous distribution of the fibres. The coupling agent effect on CPC performance was also investigated. The tensile strength and tensile modulus of the reinforced composites were significantly improved with the addition of coupling agent. The use of 10 wt.% of coconut fibres in the presence of coupling agent promote an increase on maximum tensile strength of around 41 % comparing with the HDPE/cork (50-50 wt.%) composites. Scanning electron microscopy (SEM) micrographs of the tensile fractured specimens confirmed that the use of coupling agent promoted the interfacial adhesion between the fibres and the thermoplastic matrix. Since, like cork powder, coconut fibres have good thermal and acoustic properties, we consider that the novel reinforced CPC herein described have high potential to be used in building and construction systems and other structural 3D applications.